An Investigation of the Ethical Reasoning Skills of Accountants and Career Experiences - Driskill, Trish; Tiggeman , Theresa (Journal of Accounting and Finance, 2021)
Since the myriad of financial debacles in the early 21st century, a focused interest on accountants’ ethical reasoning skills has been unsuccessful in resolving future financial crimes in the United States (Palazzo & Rethel, 2008). Unfortunately, a Price Waterhouse Cooper’s (2016) survey concluded fraud at the executive level increased by 4%. A review of the research infers inconclusive evidence of a relationship between higher ranked accounting positions and lower ethical reasoning skills when examining CPAs in the post-Sarbanes-Oxley (SOX) era, as the majority of research stems from the pre-SOX timeframe. The purpose of this quantitative, cross-sectional study was to examine various organizational levels of Certified Public Accountants (CPAs) and their ethical and social responsibility perceptions. Participants were recruited via an accounting research panel and used Singhapakdi's (1996) Perceived Role of Ethics and Social Responsibility Scale (PRESOR) to measure CPAs’ perceptions of the importance of ethics and social responsibility to an organization's overall effectiveness. The researchers’ findings indicate CPAs at mid-level positions encompass significantly different ethical and socially responsible perspectives when compared to CPAs at lower level and high-level positions within firms. Shafer (2015), using the PRESOR, found a significant relationship between accountants’ ethical perceptions and organizational ethics in a convenience study of Chinese accountants, and called for more studies using the PRESOR on accountants. This research extends the literature on accountants’ ethics and builds on Shafer’s study by employing a random sample of CPAs in the United States.